Slovenski podjetniški observatorij 2002. (2. del) - Rebernik, Miroslav; Knez Riedl, Jožica; Močnik, Dijana; Širec, Karin; Rus, Matej; Krošlin, Tadej; Tominc, Polona (University of Maribor Press, 2002)
Slovenian Entrepreneurship Observatory 2002. (Part 2). Slovenian Entrepreneurship Observatory is directly linked to the Observatory of European SMEs, which was established in 1993 under the Directorate-General XXIII, because the EU-19 recognized the need for a coordinated and integrated approach to small and medium-sized enterprises research. The report is prepared each year by the European Network for SME Research, formed by independent research institutes in the field of entrepreneurship. The basic aim of the Observatory is to track and collect data and information that are "hidden" in individual countries and make them available to other States. Slovenian Entrepreneurship Observatory follows the same methodology. Having a standard review of the Slovenian entrepreneurship demography overview in the past year, we put under the microscope the issue of tax incentives, the administrative burden on small and medium-sized enterprises in the field of employment and their social responsibility. For these topics, we conducted field research in which we analysed the answers from 1,153 companies that we have acquired through 8,176 dispatched questionnaires.